2009
DOI: 10.1128/jcm.01051-09
|View full text |Cite
|
Sign up to set email alerts
|

Mycotic Keratitis Due to Aspergillus nomius

Abstract: We report the first known case of fungal keratitis caused by Aspergillus nomius. Ocular injury was known as a predisposing factor. The patient was treated with natamycin and econazole eye drops, itraconazole eye ointment, and oral ketoconazole. A therapeutic penetrating keratoplasty was performed 16 days after presentation. A sequence-based approach was used to assign the isolate to a species. CASE REPORTA 64-year-old woman with no significant ophthalmic or systemic history presented with a history of pain, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 27 publications
0
26
0
4
Order By: Relevance
“…It was difficult for clinical microbiology laboratories to identify rarely found molds as causes of various infections. The more widespread use of ITS and other gene sequencing has enabled clinical microbiology laboratories to con- fidently identify molds that are rarely found in patients after preliminary morphological examination (13)(14)(15)(16)(17)(18)29). In addition, novel fungal species associated with clinical infections have been discovered (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was difficult for clinical microbiology laboratories to identify rarely found molds as causes of various infections. The more widespread use of ITS and other gene sequencing has enabled clinical microbiology laboratories to con- fidently identify molds that are rarely found in patients after preliminary morphological examination (13)(14)(15)(16)(17)(18)29). In addition, novel fungal species associated with clinical infections have been discovered (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…These results were also in line with those of metabolic fingerprinting, in which the A. flavus, A. nomius, and A. tamarii strains were separated into three clusters based on UHPLC MS analysis. Although A. flavus, A. nomius, and A. tamarii may (Table 2) (13)(14)(15)(16)(17)(18)29). Among the 15 strains with methods of laboratory diagnosis described in detail, all of them required molecular technologies (sequencing in 14 and high-performance liquid chromatography analysis of metabolites in 1) for identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also identified in house dust samples from Mexico [43]. This species has also been found to be able to cause human infections including onychomycosis in Italy [44], keratitis in India [22], invasive aspergillosis, cavitary and fibrosing pulmonary and pleural aspergillosis in Hong Kong [39] and breakthrough pneumonia in Italy [4]. Besides, it was also identified as the causative agent of stonebrood disease in honeybees in Great Britain [13].…”
Section: Resultsmentioning
confidence: 97%
“…Aspergillus nomius is known to be human pathogenic as it was isolated form keratitis on Coimbatore India by Manikandan et al (2009). Despite its potential as an aflatoxins producer, according to Frisvad et al (2004), Aspergillus nomius showed pharmaceutical importance to produce aspergillic acid which is most commonly known as an antibiotic and antifungal agent, pseurotin which is known to have antiparasitic and anticancer activities.…”
Section: Molecular Identification Of the Most Potent Fungal Isolate (mentioning
confidence: 99%